The Impact of Digital Communication on English Grammar and Vocabulary - WARREGH, NAJAT (Sharwes Scientific Journal, 2025)
The increase in digital communication platforms such as social media, instant notification apps and online forums has changed the way people use written English. This study checks how these digital interactions affect the grammar and vocabulary of the English language. Along with informal writing styles, the abbreviation, emojis and grammatical structures that are not standard, are increasingly common, increasingly concerned, concerns have arisen whether this development indicates a decline in linguistic innovation or language standards. The purpose of this research is to identify specific grammatical and literal changes in English as a result of digital writing practice. It also checks how users of different age groups and educational backgrounds adapt the language use in the digital environment. In addition, the study of the changes that have been seen reflects creative linguistic development or deviations from traditional criteria. Finally, it examines the possible implications of formal writing skills and digital language trends for language learning. Capturing significant changes in the use of languages ​​during the top increase of digital communication, collecting and analyzing data from selected digital platforms more than the time frame from 2010 to 2025. Conclusions provide insight into the developed nature to English in digital sites and make recommendations for teachers and language policy decision -makers to address new language trends on both academic trends and professional sales. This observe contributes to a comprehensive understanding of the way era uses language and highlights the need for up-to-date academic processes that replicate contemporary linguistic realities.